2021
DOI: 10.1037/pro0000338
|View full text |Cite
|
Sign up to set email alerts
|

Practices of prescribing psychologists: Replication and extension.

Abstract: Few studies have examined the practices of prescribing psychologists, and the extant literature suffers from small sample sizes due to the nature of the profession. The current study was based on data from 43 prescribing psychologists, the largest sample of prescribing psychologists examined to date. It was found that prescribing psychology is distinctive from both traditional psychological and psychiatric practice. Prescribing psychologists tend to work in multiple settings. Although respondents espoused a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…While it seems logical that increasing the number of prescribers would increase the number of prescriptions, it has been suggested that RxP may result in the deprescribing of psychotropic medications in patients who may see more benefits from psychotherapy or other nonpharmacologic interventions. One recent survey of prescribing psychologists found that they had decreased the dosage or removed a medication from 28.3% to 29.5% of their current patients, respectively (Peck et al, 2021), suggesting the increase in medication costs associated with this policy may be smaller than anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…While it seems logical that increasing the number of prescribers would increase the number of prescriptions, it has been suggested that RxP may result in the deprescribing of psychotropic medications in patients who may see more benefits from psychotherapy or other nonpharmacologic interventions. One recent survey of prescribing psychologists found that they had decreased the dosage or removed a medication from 28.3% to 29.5% of their current patients, respectively (Peck et al, 2021), suggesting the increase in medication costs associated with this policy may be smaller than anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…Peck et al (2021) found that “prescribing psychologists have developed a style of practice that overlaps with both psychology and psychiatry, but it is distinctive of both” (p. 199). The 43 psychologists surveyed used a combination of treatment, psychotherapy and medication, combined treatment rated as “the best option.” Sessions were shorter than nonprescribing psychologists, but longer than psychiatrists.…”
Section: Recommendationsmentioning
confidence: 99%
“…Prescribing psychologists are not psychiatrists or nurse practitioners, but rather "psychologists first and prescribers second." Peck et al (2021) found that "prescribing psychologists have developed a style of practice that overlaps with both psychology and psychiatry, but it is distinctive of both" (p. 199). The 43 psychologists surveyed used a combination of treatment, psychotherapy and medication, combined treatment rated as "the best option."…”
Section: Maintain Our Identity As Psychologists First and As Prescrib...mentioning
confidence: 99%
See 2 more Smart Citations